Colonoscopic Withdrawal Times and Adenoma Detection during Screening Colonoscopy - Barclay, Robert L; Vicari, Joseph J; Doughty, Andrea S; Johanson, John F; Greenlaw, Roger L (The New England journal of medicine, 2006)
In this study of 12 experienced gastroenterologists who performed colonoscopic screening, the duration of withdrawal of the colonoscope varied widely among physicians. Rates of detection of polyps were higher among endoscopists who took more time. These findings suggest that the effectiveness of colonoscopy in preventing colon cancer may be influenced by procedure times. In this study of colonoscopic screening, rates of detection of polyps were higher among endoscopists who took more time. In recent years, colonoscopy has become increasingly common as a screening test for colorectal neoplasia. 1 , 2 In part, this trend reflects a growing belief that colonoscopy is effective at reducing complications and death from colorectal cancer. Large prospective studies have shown substantial reductions in the expected risk of colorectal cancer during long-term follow-up after screening colonoscopy. 3 – 5 However, the magnitude of the estimated benefit of colonoscopy, in comparison with reference populations, has varied among studies. In the National Polyp Study, the estimated reduction in the incidence of colorectal cancer ranged from 76 to 90% over a prolonged period of surveillance . . .